To (Sub)Serve Man. Role Language and Intimate Scripts in Kioku no Dizorubu - Luca Bruno (Lea)
Japanese Adult Computer Games engage players in immersive narrative experiences centred on intimate interactions with anime-manga characters. Within these games, players are encouraged to develop parasocial phenomena as an integral aspect of the gameplay loop. The language employed during character interactions plays a pivotal role in shaping these parasocial phenomena, establishing specific roles, expectations, and the potential for their confirmation or subversion. This paper examines the systems of stylized character idiolects typical of anime-manga media – referred to as yakuwarigo by Kinsui 2017, 2003  – and explores how these linguistic elements embed gendered roles in the women-oriented video game Kioku no Dizorubu.